THE ROLE OF SOCIAL AND INNOVATIVE TECHNOLOGIES IN IMPROVING THE EFFICIENCY OF THE SERVICE SECTOR (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Social technologies play an important role in improving the efficiency of the service sector. By analyzing and applying various social platforms, analytics and communication tools, companies and organizations can improve the quality of service, optimize customer experience management processes, and increase customer satisfaction. Using social technologies, it is possible to create more personalized services, improve customer interaction, increase the speed of responding to requests and feedback, which ultimately contributes to business growth and competitiveness in the market.